Behavior study about teenage pregnancy and related factors in female junior and senior high school students in Jakarta - Shirley Anggraini Tunggadewi (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To get data about female teenage behavior in their sexual changes, unwanted teenage pregnancy and their negative consequences, contraception, and the relation between factors which are related to female teenage behavior. Method: Cross-sectional study at five Government Junior High Schools and five Government Senior High Schools in five regions in Jakarta. Two hundred female teenage respondents, aged between 11-17 years old, came from five Government Junior High Schools and five Government Senior High Schools in Jakarta who were picked by cluster random sampling, 20 students from each grade of school. The respondents were given questionnaires which have been validated before, and then we did scoring and statistical measurement with SPSS 13th version. Result: The respondents’ knowledge about their sexual organ changes and sexual behavior is moderate (46%), unwanted teenage pregnancy and their consequences is poor (79.5%), contraception is poor (62%) and scoring result of knowledge is poor (71%). Knowledge scoring among respondents aged between 11-14 years old is poor (85.9%), and also in age group 15-17 years old (60%). Respondents’ attitude about their sexual organ changes and sexual behavior is good (40.5%), unwanted teenage pregnancy and their consequences is good (42.5%), while contraception is poor (73.5%), and scoring result of attitude is poor (56.5%). Attitude scoring in age group 11-14 years old is poor (68.2%), and in group 15-17 years old is also poor (47.8%). Respondents’ behavior about their sexual organ changes and sexual behavior is poor (51%), unwanted teenage pregnancy and their consequences is good (66%), contraception is moderate (49%), and scoring result of behavior is moderate (49%). Attitude scoring age between 11-14 years old is moderate (55.3%), between 15-17 years old is moderate and poor (each 44.3%). The relation between behavior and the greatest impression of information source which is significant is from teacher/school (p=0.001). The relation between behavior and knowledge is only significant in age group 15-17 years old (p=0.014). There is significant relationship between behavior and attitude in age group 11-14 years old (p=0.013) and 15-17 years old (p=0.000). Determinant factor contributing to this behavior level is the information taken from their teacher/school (p=0.010). Conclusion: Respondents’ behavior about their sexual organ changes and sexual behavior is poor (51%), about unwanted teenage pregnancy and their consequences is good (66%), about contraception is moderate (49%) and scoring result of behavior is moderate (49%). Attitude scoring in age group 11- 14 years old is slightly better than in group 15-17 years old. [Indones J Obstet Gynecol 2010; 34-2: 51-8] Keywords: teenage pregnancy, unwanted pregnancy, sexual behavior, contraception